Circ-ITCH correlates with less advanced tumor features as well as prolonged survival, and it inhibits cells proliferation but promotes apoptosis in non-small cell lung cancer - Li, Zhenhua; Guo, Xiaoqun; Gao, Shan (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: This study was to investigate the correlation of circ-ITCH expression with tumor features, disease free survival (DFS) and overall survival (OS) in non-small cell lung cancer (NSCLC) patients, and the effect of its dysregulation on cells proliferation and apoptosis of NSCLC cells. Methods: Tumor tissue and paired adjacent normal tissue samples from 190 surgical NSCLC patients were collected and used for detecting circ-ITCH expression by qPCR. Circ-ITCH expression was also measured in normal pulmonary epithelial cell line and 4 NSCLC cell lines by qPCR. Patients’ baseline characteristics were recorded and DFS as well as OS were calculated. Blank, circ-ITCH overexpression, blank shRNA, circ-ITCH shRNA plasmids were transferred into NSCLC cell line (A549 cells) as NC(+), Circ-ITCH(+), NC(−) and Circ-ITCH(−) groups. Cells proliferation was measured using CCK-8 and cells apoptosis rate was measured using annexin V (AV)/propidium iodide (PI). Results: Circ-ITCH expression was decreased in tumor tissue compared with paired adjacent tissue, and was negatively correlated with tumor size, lymph node metastasis and TNM stage. And circ-ITCH high expression was associated with favorable DFS and OS. In vitro experiments revealed that compared with normal pulmonary epithelial cell line BEAS-2B, circ-ITCH expression was reduced in NSCLC cell lines HCC827, A549, NCI-H1299 and NCI-H460. And cells proliferation was decreased in Circ-ITCH(+) group and elevated in Circ-ITCH(−) group at 72 h. Cells apoptosis rate was increased in Circ-ITCH(+) group and decreased in Circ-ITCH(−) group at 72 h. Conclusions: Circ-ITCH associates with less advanced tumor features and prolonged survival, and it inhibits cells proliferation while promotes cells apoptosis in NSCLC.